Tecendo redes para acolher : oficinas de Teatro do Oprimido no atendimento clínico a estudantes universitários - Silva, Thaísa Soares (2021)
The Theater of the Oppressed methodology was proposed as a group device by the extension project “Tecendo Redes para Acolher” (weaving nets to shelter), in the form of therapeutic workshops for students living in the residence hall (CEU) of the Federal University of Mato Grosso campus Cuiabá, in the years of 2018 and 2019. This research aimed to investigate the effects, in terms of sociability, of the participation in Theater of the Oppressed (TO) workshops. The study was undertaken from a psychoanalytic theoretical framework in a clinical-qualitative research approach. The data collection instrument was carried out through semi-structured interviews with students who participated in the Theater of the Oppressed workshops at the CEU campus Cuiabá. To present the analysis of the data collected in the individual listening to the participants of this research, we selected three interviews and from some fragments we constituted the construction of the clinical case. The effects of participating in the Theater of the Oppressed workshops on the sociability of students living at CEU are noticeable in their relationships with other participants and also had an impact on the other residents of the residence hall, in other aspects of their institutional relationships and experiences in the academic context. , as reported in individual interviews. Such as relationship with professors and classmates, the choice and permanence in the undergraduate course and constitution of professional identity, dealing with contingencies related to academic life, mediation with representatives of the institutional instance, etc. We understand that with this group device, a space for reception and elaboration of individual and collective demands can be constituted. TO workshops, as an analytical listening device, proved to be an instrument that makes it possible to listen, welcome and intervene with the complexity of forms of psychic suffering in the academic context.